Improved detection and localization of insulinoma using small field-of-view diffusion-weighted MRI: A case report - Quang Trung Nguyen, BSc; Van Diep Pham, BSc; Quoc Dat Tran, BSc; Quang Long Le, BSc; Ngoc Cuong Nguyen, PhD; Tuan Linh Le, PhD (Radiology Case Reports)
Insulinoma is a rare but challenging-to-diagnose pancreatic neuroendocrine tumor, often presenting with recurrent spontaneous hypoglycemia. Surgical resection remains the definitive treatment; however, accurate preoperative localization is critical for optimizing surgical outcomes and avoiding unnecessary extensive pancreatic resection. We report a case of a 57-year-old female with recurrent hypoglycemia, whose lesion was undetectable using conventional ultrasound, computed tomography (CT), and standard magnetic resonance imaging (MRI). However, small field-of-view diffusion-weighted imaging (sFOV DWI) successfully identified a 13 × 10 mm pancreatic lesion between the body and tail, with imaging characteristics consistent with a pancreatic neuroendocrine tumor. The patient underwent successful surgical resection, with histopathological confirmation of insulinoma, leading to complete resolution of symptoms postoperatively. This case highlights the utility of sFOV DWI in detecting small pancreatic lesions that may be missed by conventional imaging techniques. Its application in challenging cases could significantly improve diagnostic accuracy and guide surgical planning.